Improving Intergroup Attitudes through Televised Vicarious Intergroup Contact: Social Cognitive Processing of Ingroup and Outgroup Information. (July 2014) - Joyce, Nick; Harwood, Jake
In an experiment, participants exposed to depictions of an intergroup interaction between a border patrolling U.S. citizen and an illegal immigrant demonstrated changed attitudes toward illegal immigrants depending on the valence of the portrayal. Negative effects were enhanced among people who identified more strongly with the U.S. citizen character, and positive effects were moderately, although nonsignificantly enhanced among those who viewed the illegal immigrant character as more typical of illegal immigrants in general. Liking of the illegal immigrant character was a significant mediator of the effects. The positive effects on attitudes toward illegal immigrants transferred to more positive attitudes toward other social groups as well. The study is framed in terms of a social cognitive theory approach to vicarious intergroup contact.